Differentiation of bovine and porcine gelatins in processed products via sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and principal component analysis (PCA) techniques - Tukiran, Nur Azira; Amin, Izzeldin; Che Man, Yaakob (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Gelatin is widely used in food and pharmaceutical products. However, the addition of gelatin especially in food products becomes a controversial issue among Muslims due to its animal origin. Thus, the present study was aimed to detect and differentiate the origin of gelatin added in processed foods using a combination method of sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and Principal Component Analysis (PCA). Porcine gelatin had exhibited 11 prominent polypeptides compared to bovine gelatin with 2 prominent polypeptides. Polypeptides of both gelatin sources at molecular weight ranged from 53 to 220 kDa can be used to differentiate between porcine and bovine gelatins using PCA. The efficiency in extracting gelatin from processed foods by different solutions was also evaluated. Extraction of gelatin in processed foods by cold acetone and deionised water had exhibited a similar polypeptide patterns, suggesting both solutions are suitable. The study indicated that approach of a simple gelatin extraction combined with SDS-PAGE and PCA, may provide robust information for gelatin species differentiation of processed foods.